Evaluation of Marriage Administration Information System Through The Sakinah Heritage Application in Sinjai Regency - Agussariman, Agussariman; Djamaluddin, A.; Rajamemang, Rajamemang (TheJournalish: Social and Government, 2024)
The research method uses qualitative, observational data collection techniques, interviews and documentation. Data analysis techniques for data reduction, data presentation and conclusion drawn. The results of the research on the evaluation of the marriage administration information system through the Pusaka Sakinah application so that the community and married couples understand the administrative information system in KUA, South Sinjai District. The marriage administration information system program through the Sakinah heirloom application in South Sinjai District by verifying the file (Administrative) to the bride-to-be and bride-to-be is held a marriage training record (Catin) so that these prospective married couples become Sakinah Mawaddah Warahmah couples, and the UCLA evaluation model in the process of convincing decisions, selecting the right information, collecting and analyzing information so that it can report a summary of the data which is useful for decision-makers and choosing several alternative marriage administration information system programs through the Pusaka Sakinah application because they have to verify files (Administrative) to prospective brides and hold marriage training which is considered to slow down the administrative system. The research output is a scientific work or reference so that it is easy for future researchers who want to research on the evaluation of the marriage administration information system through the Pusaka Sakinah application in South Sinjai Kecamatan.